Diagnostic accuracy of five different techniques for detection of approximal caries - Defne Yalçın Yeler; Melike Koraltan (Gazi University, 2018)
Objective: The aim of this study was to compare the accuracy of five different radiographic methods for the detection of approximal caries on posterior teeth. Materials and Method: Seventy-two extracted posterior teeth with and without caries were studied. Intraoral bitewing radiographs were taken with film and a storage phosphor-plate system. Extraoral panoramic images were obtained by using the bitewing, orthogonal and standard programs of a digital panoramic radiography device. Images were evaluated by two observers. Intra- and inter-observer weighted-kappa coefficients were calculated. Scores obtained from the five techniques were compared against the histological gold standard using receiver operating characteristics (ROC) curve analysis. Az values for each image type were compared using z-test and the level of statistical significance was set at 0.05. Sensitivity, specificity and false-positive rates were calculated for each method. Results: Intra- and inter-observer agreement κ values were between 0.59-0.88 and 0.54-0.87, respectively. The Az value was greatest with conventional bitewing (0.760) and phosphor plate bitewing (0.756) and lowest with standard panoramic image program (0.639). The standard panoramic image program was significantly inferior to the other diagnostic methods (p<0.05). Sensitivity and specificity values were 0.64 and 0.85 for conventional bitewing, 0.64 and 0.87 for phosphor plate bitewing, 0.40 and 0.87 for standard program, 0.56 and 0.85 for orthogonal program, and 0.59 and 0.90 for extraoral bitewing program, respectively. Conclusion: In this study, conventional and phosphor plate bitewing images were found to confer similar diagnostic accuracy. Orthogonal and extraoral bitewing programs on panoramic devices were effective for reducing superimpositions. The diagnostic sensitivity of the studied methods for approximal caries was found to be low at the level of enamel.